Student reflections on the use of 360-degree video to support pseudo-synchronous collaborative mathematical problem solving in online learning environments - Albrecht, Amie; O’Keeffe, Lisa; White, Bruce (Online Learning, 2025)
Online learning offers increased flexibility to students but also poses new complexities. For example, there are challenges in digitizing teaching approaches that rely on the co-construction of knowledge through social interaction and collaboration between learners. This study explores a novel pseudo-synchronous approach using 360-degree video to improve access to collaborative mathematical problem solving for online students. We trialed the use of 360-degree video extracts of authentic collaborative problem-solving situations to offer online learners the opportunity to engage with different approaches and methods in various mathematical problem-solving situations. Data were collected through online surveys and analyzed using descriptive statistics and thematic analysis to examine student experiences. The findings suggest students prefer face-to-face collaborative problem solving but see the value of having the 360-degree video as a support when face-to-face interaction is not available or for students choosing to engage in an online environment. The study demonstrates that pseudo-synchronous 360-degree video can provide meaningful collaborative learning experiences for asynchronous online learners.